Reason and Besinnung: Heidegger's Reflections on Science in Contributions to Philosophy. - Xiaogang, K. E. (Frontiers of Philosophy in China, 2016)
Heidegger's reflection on modern sciences in his Contributions to Philosophy is a "questioning of philosophy" instead of an analysis of a "problem of logic." Therefore, this Being-historical reflection is an ontological grounding effort of reason, instead of a rational critique of the sciences. Heidegger calls this ontological grounding a "Besinnung" or "mindful deliberation," which is one of the most important words in the Contributions. This "Besinnung" is not only a kind of "philosophy of science," but also a political critique of modern sciences.